Expanding the spectrum of EEF1D neurodevelopmental disorders: Biallelic variants in the guanine exchange domain. Issue 4 (2nd January 2023) - Averdunk, Luisa; Al‐Thihli, Khalid; Surowy, Harald; Lüdecke, Hermann‐Josef; Drechsler, Matthias; Yigit, Gökhan; Smorag, Lukasz; Al Hallak, Bassam; Li, Yun; Altmüller, Janine; Guthoff, Tanja; Wallot, Michael; et al.
Abstract: Protein translation is an essential cellular process and dysfunctional protein translation causes various neurodevelopmental disorders. The eukaryotic translation elongation factor 1A (eEF1A) delivers aminoacyl‐tRNA to the ribosome, while the eEF1B complex acts as a guanine exchange factor (GEF) of GTP for GDP indirectly catalyzing the release of eEF1A from the ribosome. The gene EEF1D encodes the eEF1Bδ subunit of the eEF1B complex. EEF1D is alternatively spliced giving rise to one long and three short isoforms. Two different homozygous, truncating variants in EEF1D had been associated with severe intellectual disability and microcephaly in two families. The published variants only affect the long isoform of EEF1D that acts as a transcription factor of heat shock element proteins. By exome sequencing, we identified two different homozygous variants in EEF1D in two families with severe developmental delay, severe microcephaly, spasticity, and failure to thrive with optic atrophy, poor feeding, and recurrent aspiration pneumonia. The EEF1D variants reported in this study are localized in the C ‐terminal GEF domain, suggesting that a disturbed protein translation machinery might contribute to the neurodevelopmental phenotype. Pathogenic variants localized in both the alternatively spliced domain or the GEF domain of EEF1D cause a severe neurodevelopmental disorder with microcephaly and spasticity. Abstract : EEF1D encodes the delta subunit of the translation elongation factor 1B and catalyzes protein translation. Formerly biallelic variants in the N‐terminal domain, that plays a role in heat shock response, were linked with neurodevelopmental disorders. Here we describe four individuals with biallelic variants in the guanine exchange domain of EEF1D .